Asociación inversa entre enfermedad de Alzheimer y cáncer - Behrens P., María Isabel; Sinning O., Mariana; Merino L., Daniela; Valdés A., María del Pilar; Zemelman D., Viviana; Donoso S., Archibaldo; Roe, Cathy; Lendon., Corinne (Revista Hospital Clínico Universidad de Chile, 2009)
The increase in life expectancy is accompanied by a concomitant increase in the prevalence of age related disorders, including neurodegenerative diseases, such as Alzheimer’s disease, Parkinson’s disease, and various types of cancers. We here report epidemiologic findings suggesting that the development of the Alzheimer and a history of cancer are inversely related. The inverse relationship was found when all cancer types were analyzed and also when skin cancers (both melanomas and those with good prognosis, that constitute 50% of all cancers) were analyzed separately. In addition, in a population study we found that this inverse relationship was found with dementia of the Alzheimer type and mixed dementia, but not with vascular dementia, suggesting that the association is only with degenerative diseases. We discuss possible explanations for this inverse relationship, among them, the possibility that a common biological mechanism might be regulated in opposite directions in neurodegenerative diseases and cancer.